Modern weapons and military equipment for issue 3/2013 - Ostojić, Nikola M. (Vojnotehnički glasnik / Military Technical Courier, 2013)
The movable robotic solar electric generator (imp-MSG), the Center for Robotics Institute "Mihajlo Pupin" in Belgrade; DARPA hidden earth sensors; Mini-Andros II robot to a dangerous situation; New oktokopter from Tekskorpa in Colombia; New Iranian armed drone; The camera in the helmet.